1985
DOI: 10.1063/1.449135
|View full text |Cite
|
Sign up to set email alerts
|

Autoionization in N2O as measured by angle-resolved photoelectron spectroscopy

Abstract: Angle-resolved photoelectron spectroscopy has been carried out on N2O as a function of photon energy from 13.5 to 20.5 eV using monochromatized synchrotron radiation. The purpose of these studies has been to investigate autoionization, and most of the data have been collected under conditions of constant ionic state. Six resonances are discussed in detail: the first four that form a portion of several Rydberg series leading to the A 2Σ+ ionic state and the first two window resonances leading to the C 2Σ+ state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Trends in the decay of these Rydberg series observable in the summed CIS presented here are summarized in table 1. The summed CIS spectra corresponding to the X and A states of the ion (figures 2 and 3) are broadly similar to the comparable CIS measurements made by Carlson et al (1985). The present measurements are also consistent with data from earlier studies using various other experimental techniques.…”
Section: Electronic Selectivity In Autoionizing Decayssupporting
confidence: 90%
“…Trends in the decay of these Rydberg series observable in the summed CIS presented here are summarized in table 1. The summed CIS spectra corresponding to the X and A states of the ion (figures 2 and 3) are broadly similar to the comparable CIS measurements made by Carlson et al (1985). The present measurements are also consistent with data from earlier studies using various other experimental techniques.…”
Section: Electronic Selectivity In Autoionizing Decayssupporting
confidence: 90%
“…as the principal quantum number of these states increases. Additionally, Carlson et al (1985) observed that the lowest four resonances showed particularly varied angular distributions. For these reasons the autoionizing decay of these lower states warranted a study with better Table 1.…”
Section: High-resolution Photoelectron Spectramentioning
confidence: 99%
“…A preliminary investigation of the decay routes of the four lowest autoionizing Rydberg states identified by Berkowitz and Eland (1977) has been performed by Carlson et al (1985). These workers recorded constant ionic state spectra corresponding to the (0, 0, 0), (1, 0, 0) 0953-4075/96/153417+17$19.50 c 1996 IOP Publishing Ltd and (2, 0, 0) vibrational levels of the X 2 state using angle-resolved photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Autoionization and predissociation have long been recognized as competitive channels in the decay of super-excited states [2]. Most of the experimental work investigating this competition in N 2 O has focused on autoionization, and numerous studies using photoelectron spectroscopy [3][4][5][6], mass spectrometry [7][8][9][10] and fluorescence spectroscopy [11][12][13][14][15][16] have enabled a good understanding of the way in which autoionization affects the valence shell photoionization dynamics to be obtained.…”
Section: Introductionmentioning
confidence: 99%